2018
DOI: 10.1186/s13046-018-0808-1
|View full text |Cite
|
Sign up to set email alerts
|

STK25-induced inhibition of aerobic glycolysis via GOLPH3-mTOR pathway suppresses cell proliferation in colorectal cancer

Abstract: BackgroundSerine/threonine protein kinase 25 (STK25) is critical in regulating whole-body glucose and insulin homeostasis and the accumulation of ectopic lipids. The Warburg effect, also known as aerobic glycolysis, is an essential metabolic characteristic of cancer cells. However, the effects of STK25 on aerobic glycolysis of cancer cells remain unexplored. The aim of this study is to investigate the role of STK25 in colorectal cancer (CRC) and to elucidate the underlying mechanisms.MethodsThe influences of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…Very strikingly, altered expression of GOLPH3 and Myosin-18A are associated with a range of malignant phenotypes including tumour secretion (41), increased trafficking to the leading edge of migratory cells and consequently augmented cell motility, loss of cell-cell adhesion and invasion (39,45,49,50,(218)(219)(220)(221)(222)(223)(224)(225). However, while this model is strongly supported by a wealth of experimental data, there is at least one report indicating that Myosin-18A is neither localised to the Golgi nor required for its characteristic ribbon like structure (226).…”
Section: Golph3 -A Golgi Pi4p Effector and Oncoproteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Very strikingly, altered expression of GOLPH3 and Myosin-18A are associated with a range of malignant phenotypes including tumour secretion (41), increased trafficking to the leading edge of migratory cells and consequently augmented cell motility, loss of cell-cell adhesion and invasion (39,45,49,50,(218)(219)(220)(221)(222)(223)(224)(225). However, while this model is strongly supported by a wealth of experimental data, there is at least one report indicating that Myosin-18A is neither localised to the Golgi nor required for its characteristic ribbon like structure (226).…”
Section: Golph3 -A Golgi Pi4p Effector and Oncoproteinmentioning
confidence: 99%
“…Hence there is a clear mechanistic pathway linking a known carcinogenic event with abnormal PI4Pdependent membrane trafficking (55). In addition, other studies have indicated that the range of non-trafficking GOLPH3 functions in cancer can be attributed to signalling activation, particularly of the AKT-mTOR signalling axis (34,39,44,49,(220)(221)(222)(223)(224)(225)(228)(229)(230)(231)(232)(233)(234)(235), and also that extra-Golgi pools of this protein that vary in size and impact depending on cell type (236). Hence, similar to the story with the Golgi PI 4-kinases, the entire repertoire of GOLPH3 dysfunctionality in cancer is unlikely to be restricted to augmented flux through the secretory pathway.…”
Section: Golph3 -A Golgi Pi4p Effector and Oncoproteinmentioning
confidence: 99%
“…STK25 suppressed aerobic glycolysis to repress cell proliferation in CRC by regulating GOLPH3-mTOR pathway [30]. Pim1 promoted CRC cell growth and tolerance to glucose starvation through enhancing the aerobic glycolysis [31].…”
Section: Discussionmentioning
confidence: 99%
“…For example, FOXC1 contributed to cell proliferation in CRC by enhancing the aerobic glycolysis through binding to FBP1 [29]. STK25 suppressed aerobic glycolysis to repress cell proliferation in CRC by regulating GOLPH3-mTOR pathway [30]. Pim1 promoted CRC cell growth and tolerance to glucose starvation through enhancing the aerobic glycolysis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we identified a potential regulatory mechanism of p16 INK4a /MMP-2 expression in cancer by loss of function of p21 WAF1/Cip1 through the interaction with hYSK1 in hypoxia (Figure 6). Conversely, Wu et al [25] have demonstrated that STK25 (a.k.a hYSK1) suppressed the proliferation of human colorectal cancer cells and silencing STK25 enhanced xenograft tumor growth in mice. Thus, additional studies are warranted to define the exact role of hYSK1 in cancer.…”
Section: Discussionmentioning
confidence: 99%